Examining unmet needs: a cross-sectional study exploring knowledge, attitudes and sexually transmitted infection screening preferences among persons who inject drugs in Camden, New Jersey. (30th June 2018) - Roth, Alexis; Tran, Nguyen Khai; Chavis, Martha; Van Der Pol, Barbara
Abstract : Objectives: To inform the development of targeted sexually transmitted infection (STI) control programmes for persons who inject drugs (PWID). Methods: We recruited 116 PWID (aged ≥ 18 years) from a community-based syringe exchange programme (SEP) and assessed their STI knowledge and screening preferences via technology assisted self-interview. We estimated prevalence of STI transmission knowledge, attitudes and screening preferences as well as the association between reported sexual behaviours (past 6 months) and willingness to self-collect specimens. Results: Participants were white (77%), female (51%) and heterosexual (77%). STI knowledge regarding transmission and testing was high among the sample. More than 70% of participants were aware extragenital infections were possible and were least likely to know urine tests do not detect rectal infections (40.9%). Site-specific specimen collection was highly reflective of reported sexual behaviour. PWID who reported receptive sex (36% vs 5%, p<0.01) and insertive anal sex (31% vs 6%, p=0.01) were more likely to collect rectal specimens than those who did not. A similar trend was seen for oral sex performance on men and self-collection of oropharyngeal swabs (15% vs 3%, p=0.04). In addition, participants preferred collecting their own sample to having a clinician collect it for them (69% vs 31%, p<0.01) and testing at the SEP compared with a STI clinic (86% vs 14%, p<0.01). Conclusion: Our findings suggest site-specific specimen collection may be a proxy for risk behaviour engagement in this fairly knowledgeable high-risk population. To increase case finding, STI control programmes should educate patients about site-specific screening and pair outreach with the infrastructure provided by SEPs, in settings where these programmes exist.